Anti-Obesity and Hepatoprotective Effects of Probiotic Goat Milk in Mice: Insights from Hepatic Proteomics - Antonela Marquez; Estefanía Andrada; Matias Russo; Jaime Daniel Babot; Roxana Medina; Paola Gauffin-Cano (Fermentation)
Dietary administration of fermented goat milk (FGM) with the starter strain Lactobacillus delbrueckii subsp. indicus CRL1447 and supplemented with different functional cultures (FCs) of lactobacilli strains (FC1: Limosilactobacillus fermentum CRL1446 + Lactiplantibacillus paraplantarum CRL1449 + Lactiplantibacillus paraplantarum CRL1472; FC2: CRL1446 + CRL1449; FC3: CRL1446 + CRL1472; and FC4: CRL1449 + CRL1472) was investigated in mice fed a high-fat diet (HFD). FGM supplemented with different FCs, referred to as Probiotic Goat Milk (PGM), demonstrated significant anti-obesity activity by reducing body weight and improving blood lipid profiles in obese mice. The animals that received the PGM showed less fat infiltration in the hepatocytes compared to the obese mice fed FGM. Hepatic proteomics data show that HFD generally upregulates proteins involved in fatty acid oxidation and downregulates proteins implicated in lipid synthesis, whereas the administration of FGM supplemented with FC3 (PGM3) improves the proteomic profile. These results suggest that PGM exerts systemic metabolic effects through modulation of the gut–liver axis, highlighting its potential as a dietary strategy against obesity-related disorders.